The Impact of Service Quality on Customer Satisfaction: A Case Study of PT. Bank Rakyat Indonesia Makassar Branch - Andi Putri Tenriyola (Jurnal Manarang Manajemen dan Bisnis, 2026)
In the current era of globalization, competition in the banking sector demands institutions to maximize operational efficiency and understand customer needs. This study aims to determine the effect of service quality specifically reliability, empathy, and assurance on customer satisfaction at PT. Bank Rakyat Indonesia (BRI) Makassar Branch. This research utilized a quantitative descriptive method. The sample consisted of 60 respondents selected through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using Multiple Linear Regression with SPSS version 25. The results reveal that reliability does not significantly affect customer satisfaction. Conversely, empathy and assurance have a significant positive impact on customer satisfaction. Simultaneously, reliability, empathy, and assurance significantly influence customer. The coefficient of determination is 0.397, indicating that these three variables explain 39.7% of customer satisfaction, while the remaining 60.3% is influenced by other unexamined factors